Navigating the Digital Marketplace: A Comprehensive Review of E-Commerce Trends, Challenges, and Innovations - Hewa Majeed Zangana; Natheer Yaseen Ali; Ayaz khalid Mohammed (TIJAB (The International Journal of Applied Business))
Background: Comprehensive exploration of e-commerce landscape; Insights drawn from diverse scholarly sources across disciplines.